PENGARUH PENYULUHAN DENGAN METODE CERAMAH DAN DISKUSI KELOMPOK TENTANG ALAT PELINDUNG DIRI TERHADAP PENINGKATAN PERILAKU PEKERJA LAS DI KECAMATAN PERCUT SEI TUAN TAHUN 2013 - Siregar, Geminsah Putra (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2014)
There are some informal welding shops in Percut Sei Tuan Subdistrict, especially at Kelurahan Kenanganand Kenangan Baru. From the preliminary survey, it has been found that there are still many employees whodo not use Personal Protection Devices (APD). The objective of the research was to know the influence ofspeech and group discussion methods in counseling on the increase of welding employees’ behavior. Thetype of the research was quasi-experiment with pretest-posttest group design; the research was conductedfrom February until May, 2013. The population was 42 welding employees at Kelurahan Kenangan andKenangan Baru, and all of them were used as the samples. The result of bivariate analysis showed that therewas the influence of speech method (p=0.000) and group discussion (p=0.000) in counseling on the increaseof the employees’ knowledge, attitude.and action. The result of multivariate analysis showed that groupdiscussion was better than speech in increasing the employees’ knowledge and attitude; it was identified bythe high level of the average grade in group discussion: 6.67>4.67 for knowledge and 18.48>13.00 forattitude (p<0.05), While the action aspect showed no significant difference to the use of personal protectivedevices by value (p = 1.000). It is recommended that the management of the Health Office in Deli SerdangDistrict as the policy maker should encourage all Public Health Centers (Puskesmas) in their working areato carry out the UKK (work health effort) program in order to increase the behavior of employees ininformal sector, especially about personal protection devices and the Department of Labor in order to moreactively monitor the informal sector workers especially workers in the use of welding personal protectivedevices. The owners of welding shops should provide personal protection devices to the employeesaccording to their specialization and supervise workers to wear personal protective devices while working